2020
DOI: 10.12928/promkes.v2i2.1900
|View full text |Cite
|
Sign up to set email alerts
|

Marital Relationship Pada Pasangan Usia Muda: Scoping Review

Abstract: There are nine percent of women aged 15-19 who have married or living together in Indonesia, one percent of women divorced in the age group of 15-19 years. This scoping review aimed to review the evidence about the marital relationship among young couple in developing countries.  Arksey and O’Malley framework was applied involving identify relevant evidence; identify review question; identify relevant evidence; study selection; charting data; and collating, summarizing and reporting the data. PRISMA flowchart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…26 Another study revealed that a good marriageable age was around 20 years for women and 25 years for men; at that age a man is an adult and can think carefully, so the men can be responsible for their household economy. 27 This is in line with a study suggesting that a man who will become a father must be able to assume the financial and economic responsibilities of the family and to have a very important involvement in the pregnancy and childbirth process contributing to positive physical and psychological health outcomes, For the mother and the child. 28 The age of the mother that is considered ideal (safe) for pregnancy and childbirth is 20-35 years old.…”
Section: Discussionsupporting
confidence: 74%
“…26 Another study revealed that a good marriageable age was around 20 years for women and 25 years for men; at that age a man is an adult and can think carefully, so the men can be responsible for their household economy. 27 This is in line with a study suggesting that a man who will become a father must be able to assume the financial and economic responsibilities of the family and to have a very important involvement in the pregnancy and childbirth process contributing to positive physical and psychological health outcomes, For the mother and the child. 28 The age of the mother that is considered ideal (safe) for pregnancy and childbirth is 20-35 years old.…”
Section: Discussionsupporting
confidence: 74%
“…Adolescents experience negative treatment, exclusion and rejection (Astuti et al, 2020b;Ngum Chi Watts et al, 2015). Young couples often experience stress and pressure in dealing with environmental and social problems (Saraswati et al, 2020)such as the impact of social stigma due to unwanted and unplanned (Afrose, 2015). Pregnant adolescents who experience exclusion will increase the risk of the prevalence of depression in adolescent mothers (Getinet et al, 2018).…”
Section: Stigma Experienced By Adolescentsduring Pregnancymentioning
confidence: 99%
“…Young married couples are more vulnerable to becoming victims of both physical and verbal violence (Jones et al, 2018). They face many environmental and social problems so they must be able to adapt to deal with the stress and pressure that arises in their family life (Saraswati & Andari Wuri Astuti, 2020).…”
Section: Introductionmentioning
confidence: 99%